EFEKTIVITAS PROGRAM KELUARGA HARAPAN (PKH) DALAM UPAYAPENGENTASAN KEMISKINAN DI DESA WIRADESA (Sahmiyya: Jurnal Ekonomi dan Bisnis, 2022)
Poverty is a complication that occurs in society, marked by the low quality of people's lives, education, health, nutrition for children under five, and sources of drinking water. Various efforts were made withthe assistance of using the Indonesian government to alleviate poverty. One of them is the Family Hope Program (PKH). This study aims to describe the effectiveness of the Family Hope Program (PKH) in poverty reduction efforts in Wiradesa village. The purpose of this research is to describe the effectiveness of PKH for poor housaeholds. The research was conducted with a qualitative descriptive type. Informants were determined purposively. Data were collected through observation, interviews, and document studies. These results confirm that the implementation of PKH in Wiradesa village has been effective when viewed from the program objectives. However, on the other hand, the focus on PKH beneficiaries in Wiradesa village cannot be said to be effective and on target.